Evaluation of hybrid 68Ga-PSMA ligand PET/CT in 248 patients with biochemical recurrence after radical prostatectomy - Eiber, Matthias; Haberkorn, Uwe; Eisenhut, Michael (Journal of nuclear medicine, 2015)
The expression of prostate-specific membrane antigen (PSMA) is increased in prostate cancer. Recently, 68Ga-PSMA (Glu-NH-CO-NH-Lys-(Ahx)-[68Ga(HBED-CC)]) was developed as a PSMA ligand. The aim of this study was to investigate the detection rate of 68Ga-PSMA PET/CT in patients with biochemical recurrence after radical prostatectomy. Methods: Two hundred forty-eight of 393 patients were evaluable for a retrospective analysis. Median prostate-specific antigen (PSA) level was 1.99 ng/mL (range, 0.2-59.4 ng/mL). All patients underwent contrast-enhanced PET/CT after injection of 155 ± 27 MBq of 68Ga-PSMA ligand. The detection rates were correlated with PSA level and PSA kinetics. The influence of antihormonal treatment, primary Gleason score, and contribution of PET and morphologic imaging to the final diagnosis were assessed. Results: Two hundred twenty-two (89.5%) patients showed pathologic findings in 68Ga-PSMA ligand PET/CT. The detection rates were 96.8%, 93.0%, 72.7%, and 57.9% for PSA levels of ≥2, 1 to <2, 0.5 to <1, and 0.2 to <0.5 ng/mL, respectively. Whereas detection rates increased with a higher PSA velocity (81.8%, 82.4%, 92.1%, and 100% in <1, 1 to <2, 2 to <5, and ≥5 ng/mL/y, respectively), no significant association could be found for PSA doubling time (82.7%, 96.2%, and 90.7% in >6, 4-6, and <4 mo, respectively). 68Ga-PSMA ligand PET (as compared with CT) exclusively provided pathologic findings in 81 (32.7%) patients. In 61 (24.6%) patients, it exclusively identified additional involved regions. In higher Gleason score (≤7 vs. ≥8), detection efficacy was significantly increased (P = 0.0190). No significant difference in detection efficacy was present regarding antiandrogen therapy (P = 0.0783). Conclusion: Hybrid 68Ga-PSMA ligand PET/CT shows substantially higher detection rates than reported for other imaging modalities. Most importantly, it reveals a high number of positive findings in the clinically important range of low PSA values (<0.5 ng/mL), which in many cases can substantially influence the further clinical management.